Subprefeituras e cidadania: um estudo sobre a percepção ambiental de moradores do Riacho Grande - Represa Billings (São Bernardo do Campo, SP) - Reis, Daniele Prado dos [UNIFESP] (2017)
The Riacho Grande subprefeitura district is located near the banks of the Billings Dam, an important area in the metropolitan area of the city of São Paulo, which is a strategic location for environmental conservation. However, historically the anthropic processes arising from the dumping of commercial and household waste directly in the water environment have interfered in the biological cycle of this region, besides the process of deforestation of native vegetation due to irregular occupations. In this perspective, the objective of this study was to analyze the perception and environmental relations of residents attending Riacho Grande subprefecture meetings, as well as to answer some questions of reflection, such as the types of demands and complaints Population has led to these meetings? Are the population concerned about the current situation in the region? Do most of them try to exercise the conservation / preservation of the environment? The environmental perception of the subjects of this research was obtained from the semi-structured questionnaires containing also their speeches through open questions. 48 collections were made in the space of the Subprefeitura. The questionnaire contained questions of environmental perception, socioeconomic characterization and related to citizenship. The results suggest that the residents are affectionate about the place and do not intend to move from the region, but they perceive that the environment is abandoned and that it needs measures against social and environmental impacts, such as deforestation, solid waste, pollution, burning and sewage In the Billings dam. For the most part, regulators agree that pollution is negatively affecting the health of residents and considers it the duty of everyone to care for the environment and to do so as much as possible during the debate and demand for Billings Dam at meetings of the Subprefeitura, being a place that can favor the exercise of the citizenship of these individuals.